Report on the Beveridge proposals
1943-01-19 1943 1940s 20 pages 3. and currency. We may perhaps disregard for this purpose the possibility of some period of heavy unemployment for a short period immediately following the end of hostilities. The process of beating swords into ploughshares may take longer than of old because modern mass production methods involve a preparatory period of many months during which jigs and tools are made and in which employment in the industries affected is bound to be temporarily restricted. When this period has been passed and surplus war stocks have been liquidated, it would seem possible that the great demands for replacement of houses, buildings and consumable goods in general should lead to a good level of employment for our people. It is, however, mainly from profitably employed and expanded capital expenditure that increasing prosperity is secured. The chief danger of large-scale unemployment will arise later on when shortages have been met and when depleted stocks have been replaced throughout the world. There may then be serious difficulties to be faced, especially in view of the possibility that the various belligerent countries may seek to turn over the capacity they have developed for war purposes to similar types of peace-time production. The task of maintaining a steady employment at a high level in such circumstances will be rendered more difficult by the fact that we cannot be content to produce for the home market alone, but must endeavour to maintain an export trade on a much larger scale than before the war. We cannot make a definite prophecy as to the future, as so much depends on International and Imperial policy and co-operation, and on our monetary policy. Reduction of Taxation. 6. In order to stimulate enterprise and employment a substantial reduction of taxation, especially the abolition of Excess Profits Tax and a reduction in the rate of Income Tax, will be essential if we are to restore the trade and business of the country and 200/B/3/2/C216/5/93